Online Multi-Domain Geriatric Health Screening in Urban Community Dwelling Older Malaysians: A Pilot Study - Alex, Deepa; Fauzi, Adhhani Binti; Mohan, Devi (Frontiers in Public Health, 2021)
Introduction: With a rapidly aging population, the Malaysian health care system needs to develop solutions to address the lack of resources that are required for the assessment of the older person. The complex nature of geriatric syndromes coupled with the occurrence of multiple comorbid illnesses with aging, make geriatric assessment a resource intensive process. Digital health solutions could play an important role in supporting existing health care systems, especially in low and middle income countries, with limited specialty services in geriatrics. Objective: This is a pilot study aimed at screening for geriatric syndromes through self-administered online surveys in urban community dwelling older Malaysians and assessing the pattern of geriatric syndromes in relation to the frailty status of the study participants. Methods: This is a cross-sectional pilot study conducted between July-September 2020. Community dwelling adults aged 60 years and over were invited to take part in an online survey. Information on sociodemographic variables, comorbidities and the self-reported results of geriatric syndromes (frailty, sarcopenia, anorexia of aging, urinary incontinence, falls, and cognitive impairment), were collected through the survey. Results: Data was collected for 162 participants over a period of 2 months. The mean (SD) age of the respondents was 66.42 (5.25) years with 64.9% females. Majority of the respondents were of Chinese ethnicity (67.9%) and had tertiary level of education (75.9%). The average time taken by participants to complete the survey was 16.86 minutes. Urinary continence was the highest reported geriatric syndrome (55.1%) followed by falls (37.6%), anorexia of aging (32.8%), cognitive impairment (27.8%) and sarcopenia (8.3%). Frailty was detected in 4.5% of the study population. Loss of weight in the previous year was the highest reported component of the frailty assessment tool. The presence of sarcopenia, anorexia of ageing, poor/fair self-rated health, urinary incontinence and multimorbidity were significantly higher in older adults who were frail or prefrail. Conclusion: Screening for geriatric syndromes through online surveys is a feasible approach to identify older adults in the community who are likely to benefit from geriatric assessment. However, the demographic profile of the older population that are accessible through such digital platforms is limited.